Case Report: Surgical Management of Painful Manubriosternal Pseudoarthrosis - Bar-Haim, Ronit; Shtarker, Haim; Biswas, Seema; Waksman, Igor; Altman, Edward (Frontiers in Surgery, 2021)
A 31-year-old male amateur bodybuilder presented with a 2-year history of chronic pain over the sternum and a clicking sensation in the chest wall on movement. Ultrasound, computed tomography (CT), and magnetic resonance imaging (MRI) showed no cause for his symptoms. Dynamic ultrasound scan performed at a specialist sports center revealed pseudoarthrosis of the manubriosternal joint (MSJ). After a period of conservative management (rest and analgesia), he failed to improve and underwent debridement and fusion of the MSJ with plates and screws. At follow-up 23 months later, he remains pain-free and has returned to weight lifting and bodybuilding.